Investigating the Relationship between Resilience and the Situation of Risk in the Face of Natural Disasters - Raeisian, Meysam; Ilanloo, Maryam; Ebrahimi, Leila (Department of Urban and Regional Planning, Diponegoro University, 2023)
Creating cities resilient in multiple dimensions could be appropriate and economic thanks to strengthening town structure to alter crises and natural and unnatural hazards. Therefore, the aim of this study is to investigate the connection between the resilience in the city of Sari and the risk situation towards natural disasters. Data analysis with geographic information system (GIS), Decision making trial and evaluation laboratory (DEMATEL), and analytic network process (ANP) is carried out. The variables studied to explain the resilience of the city of Sari are the conditions of open spaces, incompatible land uses, land bed, building resistance, access, property, density, which are evaluated in the presented paradigm. After collecting the scores and multiplying the scores by the coefficients obtained from the statistical procedures of an urban resilience model, the final computation of urban resilience in Sari was performed. The results show that its value has been calculated as 5.44398, which shows that there is an urgent need to develop programs and reform structures to increase the level of resilience in this urban area. One of the effective factors in urban resilience is the high level of social participation in crisis, which is necessary in this area. It is suggested to create educational programs in the community, so that they can maximize the level of communication and participation of employees.